H i, star formation and tidal dwarf candidate in the Arp 305 system. Issue 3 (17th April 2017) - Sengupta, Chandreyee; Scott, T. C.; Paudel, S.; Dwarakanath, K. S.; Saikia, D. J.; Sohn, B. W.
Abstract: We present results from our Giant Metrewave Radio Telescope (GMRT) H i observations of the Arp 305 system. The system consists of two interacting spiral galaxies NGC 4016 and NGC 4017, a large amount of resultant tidal debris and a prominent tidal dwarf galaxy (TDG) candidate projected within the tidal bridge between the two principal galaxies. Our higher resolution GMRT H i mapping, compared to previous observations, allowed detailed study of smaller scale features. Our H i analysis supports the conclusion in Hancock et al. that the most recent encounter between the pair occurred ∼4 × 10 8  yr ago. The GMRT observations also show H i features near NGC 4017 that may be remnants of an earlier encounter between the two galaxies. The H i properties of the bridge TDG candidate include $M_{\mathrm{H\, \small {i}}}$  ∼ 6.6 × 10 8  M⊙ and V $_{{\rm H}\, \small {i}}$ = 3500 ± 7 km s −1, which are in good agreement with the velocities of the parent galaxies. Additionally, the TDG's H i linewidth of 30 km s −1 and modest velocity gradient together with its star formation rate of 0.2 M⊙  yr −1 add to the evidence favouring the bridge candidate being a genuine TDG. The bridge TDG's Spitzer 3.6 and 4.5 μm counterparts with a [3.6]−[4.5] colour ∼ −0.2 mag suggests that stellar debris may have seeded its formation. Future spectroscopic observations could confirm this formation scenario and provide the metallicity, which is a key criterion for the validation of TDG candidates.